Fast-TrACC: A Rapid Method for Delivering and Testing Gene Editing Reagents in Somatic Plant Cells - Nasti, Ryan A.; Zinselmeier, Matthew H.; Vollbrecht, Macy; Maher, Michael F.; Voytas, Daniel F. (Frontiers in Genome Editing, 2021)
The production of transgenic or gene edited plants requires considerable time and effort. It is of value to know at the onset of a project whether the transgenes or gene editing reagents are functioning as predicted. To test molecular reagents transiently, we implemented an improved, Agrobacterium tumefaciens-based co-culture method called Fast-TrACC (Fast Treated Agrobacterium Co-Culture). Fast-TrACC delivers reagents to seedlings, allowing high throughput, and uses a luciferase reporter to monitor and calibrate the efficiency of reagent delivery. We demonstrate the use of Fast-TrACC in multiple solanaceous species and apply the method to test promoter activity and the effectiveness of gene editing reagents.